The functional group K/AC catalyst for biodiesel production / Nur Syahida Syafiqah Noralimi - Noralimi, Nur Syahida Syafiqah (2024)
Potassium activated carbon (K/AC) catalysts are attractive for transesterification and important step in the production of biodiesel. In this study, the preparation of various K/AC catalysts at different composition mass ratio (1:1, 1:3 and 1:4) in relation to the characterization and functional groups of the derived biomass K/AC which can be produced from OPKS as the carbon source. The fourier transform infrared spectroscopy (FTIR) was used to determine the important functional groups that affect the reactivity and activity of catalyst. Presence of hydroxyl (-OH), carbonyl (-C=O), and aromatic (-C=C) functional groups was observed in the results of the FTIR spectra contributing to a vital increase in catalytic activity.